2017
DOI: 10.1002/2017jd026877
|View full text |Cite
|
Sign up to set email alerts
|

Systematical Evaluation of Satellite Precipitation Estimates Over Central Asia Using an Improved Error‐Component Procedure

Abstract: Satellite precipitation estimates (SPEs) provide important alternative precipitation sources for various applications especially for regions where in situ observations are limited or unavailable, like central Asia. In this study, eight SPEs based on four different algorithms, namely, the Tropical Rainfall Measuring Mission Multisatellite Precipitation Analysis 3B42, Climate Prediction Center morphing technique (CMORPH), Global Satellite Mapping of Precipitation (GSMaP), and Precipitation Estimation from Remote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 79 publications
1
33
0
Order By: Relevance
“…In terms of statistical metrics for SPPs (Table 2), the post-real-time IMERG-F and GSMaP-Gauge generally provided the best performance at different temporal scales among all the evaluated IMERG and GSMaP SPPs, respectively (Tables 3 and 5). Post-real-time SPPs showed better performance than their near-time-time versions in several regions [36,[50][51][52][53][54][55]. However, the offset effect of positive and negative precipitation errors might lead to distorted statistical metrics.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of statistical metrics for SPPs (Table 2), the post-real-time IMERG-F and GSMaP-Gauge generally provided the best performance at different temporal scales among all the evaluated IMERG and GSMaP SPPs, respectively (Tables 3 and 5). Post-real-time SPPs showed better performance than their near-time-time versions in several regions [36,[50][51][52][53][54][55]. However, the offset effect of positive and negative precipitation errors might lead to distorted statistical metrics.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies [24,25,50,[72][73][74] found that post-real-time SPPs generally present higher quality than their near-real-time versions in many regions of the world because of gauge-based adjustment. In this study, IMERG-F evidently outperforms the near-real-time SPPs (IMERG-E and IMERG-L) in the Chindwin River basin.…”
Section: Evaluation Of Spps Against Ground Rainfall Observationsmentioning
confidence: 99%
“…The PR complemented the results of the TMI and passive microwave sensors to provide measurements of radiance through precipitating clouds along the sensor view path. Radiance frequency reflects the properties of clouds and precipitation particles [57]. The active microwave sensors provided information about cloud height by measuring a backscatter delay [57].…”
Section: Trmm Multi-satellite Precipitation Analysis (Tmpa)mentioning
confidence: 99%